Sequoyah : the Cherokee man who gave his people writing - Rumford, James, 1948-; Huckaby, Anna Sixkiller (Boston : Houghton Mifflin Co., 2004)
Contains the biography of Sequoyah, a member of the Cherokee nation who was born in the 1760s in eastern Tennessee and who developed the first written alphabet and language for the Cherokee people. Presented in English and Cherokee.
School Library Journal starred
Notable/Best Books (A.L.A.)
Horn Book Starred
2.9
K-3
Text in English and Cherokee.
Keywords: Sequoyah, -- 1770?-1843 -- Juvenile literature; Cherokee Indians -- Biography -- Juvenile literature; Cherokee language -- Writing -- Juvenile literature; Cherokee language -- Alphabet -- Juvenile literature; Sequoyah, -- 1770?-1843.; Cherokee Indians -- Biography; Cherokee language -- Writing; Cherokee language materials -- Bilingual; Cherokee language -- Alphabet; Sequoyah, -- 1770?-1843.; Cherokee Indians -- Biography; Cherokee language; Bilingual books -- English-Cherokee.; Cherokee language -- Alphabet